Apricot Rootstocks with Potential in Hungary - Edina Mendelné Pászti; Geza Bujdoso; Sezai Ercisli; Karoly Hrotkó; Ákos Mendel (Horticulturae, 2023)
In the last five decades, the use of rootstocks and scions has changed, along with their systems of cultivation. Associated with climate change, fruit trees face new ecological and phytopathological challenges. Rootstocks affect the generative and vegetative performance of a scion, such as productivity, span of nonbearing period, growth vigor, shelf-life and quality of fruits. According to a recent study, they also affect the frost tolerance of floral buds. Several traits of rootstocks facilitate the growth of a grafted tree under different climatic and soil conditions. Due to the high risks of cultivation, it is extremely important to determine which rootstocks are suitable for successful apricot production. Origin, effects on vegetative and generative traits, tolerance, resistance and adaptability of rootstocks are summarized in this review to select suitable rootstock for apricot cultivars under Hungarian conditions.